2016
DOI: 10.1088/0953-8984/28/48/486004
|View full text |Cite
|
Sign up to set email alerts
|

Interface mixing and its impact on exchange coupling in exchange biased systems

Abstract: Exchange bias and interlayer exchange coupling are interface driven phenomena. Since an ideal interface is very challenging to achieve, a clear understanding of the chemical and magnetic natures of interfaces is pivotal to identify their influence on the magnetism. We have chosen NiFe/CoO(t )/Co trilayers as a model system, and identified non-stoichiometric Ni-ferrite and Co-ferrite at the surface and interface, respectively. These ferrites, being ferrimagnets typically, should influence the exchange coupling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 67 publications
0
7
0
1
Order By: Relevance
“…13. The Ar-bombarded (herein referred to as Ar-LSMO) and the O 2+ /Ar + bombarded (herein referred to as O 2 -Ar-LSMO) LSMO layer were obtained by treatment with argon (Ar) or a mixture of oxygen (O 2 ) and Ar gases (O 2 /Ar ∼35%) from an End-Hall ion source (V EH = 70 V, 500 mA) 21,22 for 20 min each in order to etch away (etching rate ∼0.3 nm/min) the outermost atomic layers of the LSMO surface.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…13. The Ar-bombarded (herein referred to as Ar-LSMO) and the O 2+ /Ar + bombarded (herein referred to as O 2 -Ar-LSMO) LSMO layer were obtained by treatment with argon (Ar) or a mixture of oxygen (O 2 ) and Ar gases (O 2 /Ar ∼35%) from an End-Hall ion source (V EH = 70 V, 500 mA) 21,22 for 20 min each in order to etch away (etching rate ∼0.3 nm/min) the outermost atomic layers of the LSMO surface.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Наличие у этих металлов f -оболочек, обладающих высоким значением орбитального момента, позволяет усиливать обмен между слоями магниторезистивных элементов за счет увеличенной энергии спин-орбитального взаимодействия. Мы полагаем, что увеличение поля смещения в структурах с немагнитной прослойкой Ta связано с РККИ компонентой обмена смещения, доказательства существования которой рассматривались в работах [36,37].…”
Section: результаты и обсуждениеunclassified
“…However, it has been known that atomic intermixing at the interface or the sharpness of the interface plays an important role in the exchange coupling , between AFM/FM heterostructures. Dimitriadis et al have shown theoretically the atomic scale roughness at the interface that leads to the reduction of uncompensated spins resulting in suppression of H E .…”
Section: Introductionmentioning
confidence: 99%